Ethnicity as an Agent of Production of Plastic art in Latin America: Discrimination and Multiculturalism - Campuzano Cruz, Olivia (2019)
The present work was carried out with the purpose of analyzing ethnicity, from its symbolic load and its social implications, as a powerful influence in Latin American plastic art; this with the intention of reflecting and dimensioning their implications and the cultural effects they produce. In general, the analytical, synthetic and concordance methods were used for the establishment, structuring and development of the research, particularly iconographic and iconological methods for the analysis of the plastic work were applied of Gustavo Toaquiza (1971, Ecuador) and Gilberto Delgado (1987, México)). Our results show indigenous plastic art as a reflection of the collective entities that give rise to it, as a cultural product that debates, denounces and it is placed as an element of interaction that combats discrimination and helps understanding of a multicultural Latin America.